Urinary tract infection in non-hospitalized patients with cirrhosis and no symptoms of urinary tract infection: a case series study - Cruz,Rita de Cássia Reis (2006)
Bacterial infections are important factors in decompensation, and they increase the mortality rate of patients with liver cirrhosis. The most common infections among these patients are spontaneous bacterial peritonitis, pneumonia, skin infections and urinary tract infections (UTI). This transversal study evaluated the frequency of UTI in non-hospitalized patients with cirrhosis followed in a hepatology outpatient unit. Patients with clinical, laboratorial, echographic and/or histological diagnosis of cirrhosis were evaluated from April 2002 to August 2004. Patients who accepted participating in this study were submitted to clinical evaluation and the following laboratorial examinations: urine analysis, urine culture, blood culture and hepatic function tests. Patients with symptoms of UTI, diabetis, prostatic disease were excluded. Eighty-two patients with cirrhosis were studied. Their mean age was 51 years (SD = 11); 73% were male. Hepatitis C virus was the main etiology in 45% of the cases. The Child-Pugh B functional class was observed in 52% of the cases. Urine cultures were positive in 4.9% of these patients. In this study of non-hospitalized cirrhotic patients, with no symptoms of UTI, the frequency of urinary tract infection was approximately 5%. The bacteria found were E. coli and Klebsiella pneumonia. We conclude that it is necessary to screen for UTI in such patients.